2017
DOI: 10.1148/radiol.2017162776
|View full text |Cite
|
Sign up to set email alerts
|

Single-Session High-Intensity Focused Ultrasound Treatment for Persistent or Relapsed Graves Disease: Preliminary Experience in a Prospective Study

Abstract: Purpose To evaluate the safety and efficacy of ultrasonography (US)-guided high-intensity focused ultrasound (HIFU) ablation as a treatment for medically refractory Graves disease (GD). Materials and Methods After ethics approval, a prospective trial (NCT02685514) was performed from November 2015 to February 2016. Thirty patients underwent ablation of the entire right and left thyroid lobes, with areas near the tracheal-esophageal groove and common carotid artery left unablated. Serum thyroid-stimulating hormo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 28 publications
0
13
0
1
Order By: Relevance
“…Procedure-related major complications including recurrent laryngeal nerve paralysis and Horner syndrome occurred in two and one cases, respectively. Since the recurrent laryngeal nerve was close to the treated nodule when it was located in the danger triangle, we believe it was a technical error caused by directing the thermal energy too close to this region [ 23 ]. Horner syndrome, presenting as a combination of ptosis, miosis, and anhidrosis of the face, could be caused by thermal injury to the middle cervical sympathetic ganglion (mCSG) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Procedure-related major complications including recurrent laryngeal nerve paralysis and Horner syndrome occurred in two and one cases, respectively. Since the recurrent laryngeal nerve was close to the treated nodule when it was located in the danger triangle, we believe it was a technical error caused by directing the thermal energy too close to this region [ 23 ]. Horner syndrome, presenting as a combination of ptosis, miosis, and anhidrosis of the face, could be caused by thermal injury to the middle cervical sympathetic ganglion (mCSG) [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Gambelunghe et al [19] suggested that complete ablation (or a very high percentage of ablation) is essential to achieve a marked reduction in the thyroid nodule. In a high intensity focused ultrasound study of mild Graves' disease, Lang et al [36] hypothesized that the ablation volume ratio may be a factor in disease relapse.…”
Section: Advances In Techniques For Reducing Marginal Regrowthmentioning
confidence: 99%
“…Lang B.H. et al applied HIFU into benign thyroid diseases such as Gravels Disease 55 and large-size benign thyroid nodules 56, HIFU had excellent safety and efficacy in treating thyroid disorders above. However, in PTMC field, the HIFU research was not published yet and needed researcher to investigate step by step.…”
Section: Other Technologiesmentioning
confidence: 99%